2019
DOI: 10.1111/nph.15748
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet biogenesis regulated by the FgNem1/Spo7‐FgPah1 phosphatase cascade plays critical roles in fungal development and virulence in Fusarium graminearum

Abstract: Summary Lipid droplets (LDs) control lipid metabolism in eukaryotic cells in general. However, the biogenesis regulation and biological functions of LDs are largely unknown in pathogenic fungi. Rapamycin treatment results in a significant increase of LD biogenesis in Fusarium graminearum. Molecular mechanisms of the target of rapamycin (TOR) pathway in regulating LD biogenesis and the functions of LD in virulence of F. graminearum were investigated in depth by combining genetic, cytological and phenotypic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…The reduction of glycerol production in Δ FgSah1 also explained its increased sensitivity to fludioxonil and iprodione, which have been reported to be related to osmotic pressure [ 50 ]. The lack of glycerol in deletion mutants leads to a sharp decrease in the synthesis of LDs, which has been reported to be crucial to full virulence and proper development [ 57 ]. We inferred that FgSah1 may be partly responsible for the impaired infection abilities on the host due to the deficient lipid metabolism in mutant strains.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of glycerol production in Δ FgSah1 also explained its increased sensitivity to fludioxonil and iprodione, which have been reported to be related to osmotic pressure [ 50 ]. The lack of glycerol in deletion mutants leads to a sharp decrease in the synthesis of LDs, which has been reported to be crucial to full virulence and proper development [ 57 ]. We inferred that FgSah1 may be partly responsible for the impaired infection abilities on the host due to the deficient lipid metabolism in mutant strains.…”
Section: Discussionmentioning
confidence: 99%
“…The ER plays a role in the biosynthesis of DON, which requires the formation of toxisomes on the ER (11), a large organelle with various key functions. Recent studies have shown that the formation of toxisomes is related to the generation of LDs during DON biosynthesis in vitro and in planta (37). LDs are also produced in the ER, and Atl1, as an ER-associated protein, has been shown to regulate the size of LDs in mammalian cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…FgSey1 is involved in formation of lipid droplets and toxisomes. During plant infection, a large number of LDs, which are associated with toxisome formation, are synthesized in F. graminearum (37). In eukaryotes, LDs are synthesized on endoplasmic reticulum, while the mammalian dynamin-like GTPase protein atlastin, ATL1 (the ortholog of FgSey1), is involved in the regulation of normal LD formation (20).…”
Section: Saccharomyces Cerevisiae Sey1mentioning
confidence: 99%
See 1 more Smart Citation
“…LDs contain dozens of different proteins on their surfaces, form tight associations with other organelles and cellular structures, and play essential roles in diverse cellular processes such as energy homeostasis, oxidative stress, detoxification, membrane stability, and gene regulation [ 28 , 29 , 30 , 31 , 32 ]. A number of bacterial and fungal pathogens use their own lipid droplets, or exploit host lipid droplets, as a means of initiating and maintaining infection [ 33 , 34 , 35 ]. The rice blast fungus, Magnaporthe grisea , for instance, mobilizes lipid droplets during infection structure (appressoria) formation, where they are degraded for use as energy stores and for maintaining the extremely high turgor pressure necessary to infect its host by mechanical penetration of tissues [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%